MARKETING MIX OF 4P'S FOR CUSTOMER PURCHASING DECISIONS - Sukanta, Sukanta; Wahyudin; Muhammad Abdul Muis (Dinasti Publisher, 2022)
The aim of this study was to analyze the impact of product, price, location and advertising on consumer purchasing decisions using the Go Food app in 2022. The survey technique used. a quantitative. technique .the use of. cross-sectional records and number one records from the questionnaire. Mechanical sampling makes use of a centered sampling technique. The records evaluation strategies used are multiple regression to check validity, reliability check, normality check, classical recognition check (multicollinearity check, heterogeneous dispersibility check), and 5% importance level. Hypothesis check records. and records to examine. the effect. The outcomes of this take a look at display that the subvariables Product, Price, Price, and Promotion have a high-quality and huge effect on consumers' shopping selections while the use of the GoFood utility. One of the maximum dominant variables is the product. On the opposite hand, product, price, location, and marketing and marketing unbiased variables have essential in addition to based variables in purchaser shopping selections the use of the GoFood utility. The coefficient of dedication for this take a look at indicates 58%. This indicates that fluctuations withinside the unbiased variables Product, Price, Place, and Promotion can give an explanation for a 58% boom or lower withinside the fluctuations withinside the based variable withinside the purchaser's shopping choice the use of the Go-Food utility, whilst the rest. 58% are tormented by different unbiased variables.